2006
DOI: 10.1002/jnr.20747
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ERK and JNK activity by transient forebrain ischemia in rats

Abstract: The mitogen-activated protein (MAP) kinase families of ERK and JNK participate in numerous intracellular signaling pathways and are abundantly expressed in the CNS. Activation of ERK and JNK during reperfusion of ischemic tissue is implicated in promoting cell death, insofar as inhibition of either pathway reduces neuronal cell death. However, ERK or JNK activation provides protection in other neuronal injury models. In this study, we monitored the concurrent modulation of ERK and JNK activity in the hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 64 publications
4
15
0
Order By: Relevance
“…10,[28][29][30][31] We confirmed that ERK1/2 and JNK signaling were activated during hypoxia and following reoxygenation. 32, 33 We further found that SsnB indeed suppressed the activation of these two pathways during hypoxia and reoxygenation.…”
Section: Discussionsupporting
confidence: 87%
“…10,[28][29][30][31] We confirmed that ERK1/2 and JNK signaling were activated during hypoxia and following reoxygenation. 32, 33 We further found that SsnB indeed suppressed the activation of these two pathways during hypoxia and reoxygenation.…”
Section: Discussionsupporting
confidence: 87%
“…The inset shows that this dose of tautomycin has no effect on LTD in control slices. postischemic brain, the level of phosphorylated, activated ERK1/2 and JNKs was reported to rapidly increase (Farrokhnia et al, 2005;Shackelford and Yeh, 2006), and inhibition of ERK1/2 or JNKs suppresses neuronal injury after transient or permanent MCAO in the rat (Alessandrini et al, 1999;Borsello et al, 2003). However, the actual pathways linking the initial steps of excitotoxicity to ERK/JNK activation and apoptotic processes remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…JNK1 and JNK2 are expressed in all tissues and are required for normal brain development. Furthermore, JNK1 displays constitutive activity in the CNS and is required to maintain microtubule integrity in axons and dendrites in the adult animal [272]. In contrast, JNK3 is specifically implicated in promoting neuronal cell death, in that targeted deletion of JNK3 protects mice from brain injury after cerebral ischemiahypoxia [273].…”
Section: C-jun N-terminal Kinase-mediated Apoptosismentioning
confidence: 98%